Encyclopedia of Structural Health Monitoring 2008
DOI: 10.1002/9780470061626.shm086
|View full text |Cite
|
Sign up to set email alerts
|

Sensor Placement Optimization

Abstract: Structural health monitoring (SHM) systems depend critically on using the correct number of sensors and on positioning them appropriately on the structure. A rigorous approach to this problem requires an optimization methodology as described in this article. The article begins with a definition of the problem and provides a literature review covering relevant methodologies. The basic theories of the main approaches are then discussed in more detail. Finally, the article provides an illustrative case study of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…In 2009 an excellent overview of existing techniques for optimal sensor placement was published by Barthorpe and Worden [8]. Recently, Zhou et al [9] have proposed a software architecture implementing four approaches for OSP, namely: mode shape difference, Effective Independence, information entropy and modal energy.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009 an excellent overview of existing techniques for optimal sensor placement was published by Barthorpe and Worden [8]. Recently, Zhou et al [9] have proposed a software architecture implementing four approaches for OSP, namely: mode shape difference, Effective Independence, information entropy and modal energy.…”
Section: Introductionmentioning
confidence: 99%
“…Information-based OSP methods have been studied by many researchers, in which the optimal sensor locations are so selected that they maximize the norm of the Fisher information matrix or its variants to provide maximum information on the state of a structure [8][9][10]. Barthorpe and Worden [11] provided a comprehensive review on OSP methods.…”
Section: Introductionmentioning
confidence: 99%
“…Where the problem is to select the most effective subset of sensors from a large candidate set, the problem is one of combinatorial optimisation, and such problems are notoriously difficult. A good survey of the literature of optimal sensor placement can be found in [1], a more recent survey in the context of civil infrastructure is [2].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a smaller number of sensors can provide sufficiently accurate locations, if they are positioned optimally, and the sensor data are correctly processed [3]. It is useful here to distinguish between the problem of impact detection and location and the more general problem of damage detection (as discussed in [1]). Damage detection can often be carried out by off-line methods when the system or structure is out of service.…”
Section: Introductionmentioning
confidence: 99%